Design of Mortality Data Processing Information System to Support Accuracy of Mortality Reporting at Hermina Arcamanik Hospital - Dita Alfiani Widi Saputri; Yuda Syahidin; Sali Setiatin (International Journal of Information Engineering and Science, 2025)
Technology that develops very rapidly brings many changes, especially in the development of medical records in hospitals that are increasing. Electronic medical records bring many benefits, one of which is improving the quality of services in hospitals. The medical records used at Hermina Arcamanik Hospital are mostly electronic-based, including reporting. However, problems were found in the medical record installation, namely, there were several reports that had not been managed optimally. This is because reporting still uses google spreadsheets which requires data to be moved manually one by one, so it takes a long time, and the quality of reporting becomes less accurate. A real example of this problem can be seen in the process of reporting patient Mortalitys. Meanwhile, accurate and systematic reporting of Mortality data is essential in supporting decision-making in hospitals. Therefore, the design of a patient Mortality reporting information system is urgently needed to make time efficient and improve the quality of reports. The method used in designing this system is extreme programming and web-based. The results of this information system design are able to shorten the time to make Mortality reports and can produce accurate data